Implementing high-speed running and sprinting training in professional soccer - Beato, M.; Drust, B.; Iacono, A. D. (International Journal of Sports Medicine, 2021)
High-speed running and sprinting training play an important role in the development of physical capabilities, sport-specific performance and injury prevention among soccer players. This commentary aims to summarize the current evidence regarding high-speed running and sprinting training in professional soccer and to inform its implementation in research and applied settings. It is structured into four sections: 1) Evidence-based high-speed running and sprinting conditioning methodologies; 2) Monitoring of high-speed running and sprinting performance in soccer 3) Recommendations for effective implementation of high-speed running and sprinting training in applied soccer settings; 4) Limitations and future directions. The contemporary literature provides preliminary methodological guidelines for coaches and practitioners. The recommended methods to ensure high-speed running and sprinting exposure for both conditioning purposes and injury prevention strategies among soccer players are: high-intensity running training, field-based drills and ball-drills in the form of medium- and large-sided games. Global navigation satellite systems are valid and reliable technologies for high-speed running and sprinting monitoring practice. Future research is required to refine, and advance training practices aimed at optimizing individual high-speed running and sprinting training responses and associated long-term effects.